New anti-pseudomonal agents for cystic fibrosis- still needed in the era of small molecule CFTR modulators?. (13th August 2018) - Davies, Jane C.; Martin, Isaac
ABSTRACT: Introduction : Cystic fibrosis is characterized by bacterial lung infection, a majority of adults being chronically infected with Pseudomonas aeruginosa . Treatment is a major challenge, with frequent courses of antibiotics contributing to antimicrobial resistance. New approaches are clearly required. Over the last few years, a major shift in our approach to treating CF has occurred with the availability of the first drugs targeting the CFTR protein and leading to improvements in lung function, weight gain and frequency of exacerbations. Areas covered : There are emerging, but limited, data exploring the effect these drugs have on airway infections, some studies suggesting a beneficial impact. CFTR modulators probably possess very little direct antimicrobial activity, but both synergy with conventional antibiotics and alternative mechanisms of bacterial killing have been proposed. This article reviews the current published evidence. Expert opinion : The picture is far from clear concerning the impact of CFTR modulators on lung infections. However, currently, such drugs restore CFTR function incompletely, are most commonly introduced when lung damage is already present, are not suitable for all CF patients and not reimbursed in some areas. Therefore, whatever their eventual anti-infective potential, we need to continue our search for effective anti-pseudomonal therapies for the foreseeable future.